2012
DOI: 10.1136/jech-2011-200047
|View full text |Cite
|
Sign up to set email alerts
|

School dropout: a major public health challenge: a 10-year prospective study on medical and non-medical social insurance benefits in young adulthood, the Young-HUNT 1 Study (Norway)

Abstract: The strong association between poor self-rated health in adolescence, high school dropout and reduced work integration needs attention and suggests preventive measures on an individual as well as on a societal level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 25 publications
6
95
2
5
Order By: Relevance
“…Self -rated health: A strong association was found between poor selfrated health, school dropout and risk of receiving medical or non -medical benefits (De Ridder et al, 2012). Another study found that self -rated health status had an impact on success with later employment (Hammer 1997).…”
Section: Summary Of Associationsmentioning
confidence: 99%
“…Self -rated health: A strong association was found between poor selfrated health, school dropout and risk of receiving medical or non -medical benefits (De Ridder et al, 2012). Another study found that self -rated health status had an impact on success with later employment (Hammer 1997).…”
Section: Summary Of Associationsmentioning
confidence: 99%
“…Oppfølging av denne gruppen fra skolehelsetjenesten kan vaere viktig for å forebygge forverring og tilrettelegge for å styrke HRLK og egenvurdert helse. Det vises til at det er sammenheng med dårlig selvrapportert helse hos ungdom og frafall i skolen (29). Spesielt overganger er utfordrende.…”
Section: Introduksjonunclassified
“…Man peker på at jenter har lavere psykososial helse og selvtillit (9,19), og forskning viser også at det er jenter som uttrykker mest somatisering av psykososiale problemer (10,15,29). Forskning på mulige årsaker til kjønnsforskjeller i HRLK peker på at kvinner synes å oppleve sterkere emosjonell intensitet enn menn.…”
Section: Introduksjonunclassified
“…Also, children with less severe problems who do not meet criteria for a psychiatric disorder, have increased risk of adverse outcomes [13]. The probability of young people returning to employment after receiving health-related benefits in their early years is low [2,4], thus they are in danger of social exclusion and marginalisation. Therefore, studying mechanisms and identifying possible factors that may be targets for prevention aiming to reduce the receipt of medical benefits in young adulthood are important, both from a socio-economic and from an individual perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, the unemployment rate is low, but the proportion of young adults receiving medical benefits is worrying [2]. School drop-out is prevalent [3], and is a risk factor for welfare dependency [4]. Mental health problems are a major contributor to health related disability in children and youth [5,6], and mental health problems in adolescence are risk factors for school drop-out [3,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%